Role of cholesterol 7alpha-hydroxylase (CYP7A1) in nutrigenetics and pharmacogenetics of cholesterol lowering - Hubacek, Jaroslav A; Bobkova, Dagmar (Molecular diagnosis & therapy, 2006)
The relationship between dietary composition/cholesterol-lowering therapy and final plasma lipid levels is to some extent genetically determined. It is clear that these responses are under polygenic control, with multiple variants in many genes participating in the total effect (and with each gene contributing a relatively small effect). Using different experimental approaches, several candidate genes have been analyzed to date.Interesting and consistent results have been published recently regarding the A-204C promoter variant in the cholesterol 7alpha-hydroxylase (CYP7A1) gene. CYP7A1 is a rate-limiting enzyme in bile acid synthesis and therefore plays an important role in maintaining cholesterol homeostasis. CYP7A1-204CC homozygotes have the greatest decrease in total cholesterol level in response to dietary changes in different types of dietary intervention studies. In contrast, one study has reported that the effect of statins in lowering low-density lipoprotein (LDL)-cholesterol levels was slightly greater in -204AA homozygotes. The CYP7A1 A-204C variant accounts for a significant proportion of the genetic predisposition of the response of plasma cholesterol levels.
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; anticholesteremika; statiny; kardiovaskulární nemoci; Cholesterol 7-alpha-Hydroxylase; Cholesterol, LDL; farmakogenetika; Humans; Cardiovascular Diseases; Eating; přijímání potravy; lidé; Pharmacogenetics; Anticholesteremic Agents; dieta; cholesterol-7-alfa-hydroxylasa; Diet; LDL-cholesterol